The courageous leader : how to face any challenge and lead your team to success - Sebaly, Angela (Wiley, 2017)
"The Courageous Leader is about being Courageous in the face of tough times. Courage is defined as & ldquo;what moves us to action in the face of tough times. & rdquo; Tough times are defined as & ldquo;situations and people that cause us some level of discomfort or pain. & rdquo; So the question for every leader who wants to personify the Spine of a Leader is: & ldquo;Are you willing to move to action in the face of discomfort or pain? & rdquo; It & rsquo;s not that courageous leaders derive pleasure from pain, but rather, that they are willing to accept pain as part of the process. Traditionally, courage has been viewed as something reserved for the elite and well trained. Leaders falsely believe they are required to be the & ldquo;Navy Seals & rdquo; of the workplace to be considered courageous but in reality, courage is accessible to everyone. Courage is required not just with the grandiose problems but in the simple every day challenges that we all have the capacity to tap into. The Courageous Leader provides a different lens for how to see and leverage courage in day to day application by using stories of every day leaders"--